Implementation of Differentiated Learning Management in Indonesian Junior High School Education - Septrina, Eka; Hermita, Neni; Erlisnawati`, Erlisnawati (Journal Of Teaching And Learning In Elementary Education, 2024)
This study aims to analyze the implementation of differentiated learning management at SMP Negeri 42 Pekanbaru in the context of the Kurikulum Merdeka. This curriculum was launched to address the "learning loss" due to the COVID-19 pandemic and to catch up with Indonesia's educational lag at the international level. Differentiated learning is a strategy that adjusts the learning process to the individual needs of students, taking into account their interests, readiness, and learning profiles. The research method used is a case study with a qualitative approach, involving observations and in-depth interviews with teachers at SMP Negeri 42 Pekanbaru. The results show that most teachers still experience difficulties in implementing differentiated learning according to the guidelines provided by the Ministry of Education. The main obstacles include a lack of understanding of the principles of differentiated learning and limited resources. However, some teachers have successfully adapted this method and reported an increase in student learning motivation. The study concludes that further support from the government and ongoing training is needed to optimize the implementation of differentiated learning in schools. The implications of this study are expected to provide insights for the development of more effective educational policies about learning differentiation in the future.